Development of pop book media with augmented reality features in improving students' creative writing skills in elementary schools - Raihani Afifah; Moh. Farizqo Irvan; Lavia Zahra Sabila; Dian Apriliya Andriyani; Adreng Sayekti; Putri Nur Aurora; Anggian Ristianto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
Decrease in Indonesia's PISA scores in 2015, 2018 and 2022. Creative competence can be improved through creative writing skills. This research aims to develop and test the feasibility of pop-up book media with augmented reality features in improving elementary school students' creative writing skills. The subject of this research is the assessment of media and material practitioners. The method used is the ADDIE model. The data collection techniques are observation, interviews, questionnaires, and scoring. The assessment instrument is a validation sheet from media and material experts. Using quantitative data analysis techniques. The results of the validation and assessment of media and material practitioners obtained a score from media experts of 70% in the appropriate category and from material experts of 85% in the very appropriate category. Thus, it can be concluded that pop-up book media with augmented reality features is very suitable as an alternative solution to support the creative writing skills of elementary school students. Future researchers should be able to use the results of this research as a basis for testing the effectiveness of the augmented reality pop-up book media feature in improving elementary school students' creative writing abilities.